Ornithodoros (Alectorobius) puertoricensis (Ixodida: Argasidae) parasitizing exotic reptile pets in Panama (FAVE Sección Ciencias Veterinarias, 2015)
In this paper we report and discuss the finding of all the stages of Ornithodoros puertoricensis (Argasidae) parasitizing the exotic reptiles Varanus dumerilii, Python regius and P. bivittatus, and its presence in the reptiles’ terrariums in Panamá city.
Keywords: Ornithodoros puertoricencis; exotic reptiles; Panama